Revision of the Australian Andini (Hemiptera: Fulgoromorpha: Cixiidae) with a description of five new species - Löcker, Birgit; Fletcher, Murray J.; Holzinger, Werner E.; Gurr, Geoff M. (Zootaxa, 2007)
Andini, a tribe comprising two genera, Andes Stål, 1866 and Parandes Muir, 1925, is primarily distributed through the tropical and subtropical regions of South East Asia, Australia and Africa. One species, Andes migratorius (Distant, 1907), was previously known from Australia, the following five Australian species are herein described as new: Andes dossenus sp. nov., A. ikelus sp. nov., A. lamondensis sp. nov., A. moaensis sp. nov. and A. turrondi sp. nov. Lectotypes are designated for Brixia migratoria Distant, 1907 and Leirioessa tortricomorpha Kirkaldy, 1907. Maps of the known distribution for each species are given and the close links between the Australian and Asian fauna are discussed.